2015
DOI: 10.1038/cgt.2015.34
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligonucleotide targeting eukaryotic translation initiation factor 4E reduces growth and enhances chemosensitivity of non-small-cell lung cancer cells

Abstract: Elevated levels of eukaryotic translation initiation factor 4E (eIF4E) enhance translation of many malignancy-related proteins, such as vascular endothelial growth factor (VEGF), c-Myc and osteopontin. In non-small-cell lung cancer (NSCLC), levels of eIF4E are significantly increased compared with normal lung tissue. Here, we used an antisense oligonucleotide (ASO) to inhibit the expression of eIF4E in NSCLC cell lines. eIF4E levels were significantly reduced in a dose-dependent manner in NSCLC cells treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…eIF4E stimulates the nuclear transport of mRNAs housing an eIF4E-sensitivity element. Notably, these mRNAs encode proteins associated with growth and malignancy [18]. For example, eIF4E regulates the expression of E3 ubiquitin-protein ligase, an important negative regulator of p53.…”
Section: Dual Targeting Of Mnks Reviewmentioning
confidence: 99%
“…eIF4E stimulates the nuclear transport of mRNAs housing an eIF4E-sensitivity element. Notably, these mRNAs encode proteins associated with growth and malignancy [18]. For example, eIF4E regulates the expression of E3 ubiquitin-protein ligase, an important negative regulator of p53.…”
Section: Dual Targeting Of Mnks Reviewmentioning
confidence: 99%
“…The c-Myc protein has a short half-life of ,30 minutes, 4 and the complex secondary structures in the 59 untranslated region (UTR) of MYC messenger RNA (mRNA) make its translation highly dependent on the eukaryotic translation initiation factor 4F (eIF4F). 5,6 eIF4F exists as a complex composed of the eIF4E, eIF4A, and eIF4G subunits. eIF4E can be sequestered by eIF4E-binding protein 1 (4E-BP1), which acts as a "brake" for initiation of mRNA translation.…”
mentioning
confidence: 99%
“…As these weak mRNAs almost universally encode growth regulatory proteins, including C-myc, Cyclin D1, Bcl-2, Survivin, FGF-2, VEGF, and MMP-9 etc [5, 10]. They were reported to promote the tumor cells resistance to apoptosis, proliferation, invasion and distant metastasis, even drug resistance induced by increased eIF4E [10, 1417]. The present study have clarified the oncogenic role of eIF4E in ESCC, and confirmed that the weak mRNAs including C-myc, Cyclin D1, Bcl-2, Survivin, FGF-2, VEGF, and MMP-9 were regulated by eIF4E in ESCC cell line.…”
Section: Resultsmentioning
confidence: 99%
“…Proliferation of malignant tissue needs variable proteins continual synthesis, thus over-expression of eIF4E is an inevitable event. Recent studies have revealed that excessive eIF4E could change cell phenotype and participate in the induction of cell proliferation, cell transformation and tumorigenesis, invasion and metastasis [10, 1417]. Excessive expression of eIF4E is significantly correlated with unfavorable clinical outcomes such as pathological grading of tumor, high cellular proliferation, and poor prognosis in several cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation